Estandarización de los modelos analíticos de inyección de polímeros mediante una herramienta digital (2020)
Every day, the oil industry resorts more often to improved recovery processes, due to the decrease in new hydrocarbon significant findings and the need to meet the growing demand. An important technique within these processes is the polymer flooding, which improves the mobility ratio and increases the oil sweep to the producing wells. This technique means an additional cost in the operation for which it is necessary to estimate its viability, for this purpose, different tools are used such as the numerical simulation that allows to predict almost all the phenomena involved in this process, but require a large amount of information for its use, there are also analytical models that offer approximated results, with the advantage that they need little information, which make them useful at the beginning of the improved recovery projects. Therefore, the objective of this thesis is to standardize a methodology for a series of analytical models for polymer flooding using a digital tool.